Stability and Survival of the Banking Sector in Indonesia - Agnes Melissa Sitepu; Farida Titik Kristanti (Asean International Journal of Business, 2026)
Purpose – This paper seeks to examine the stability and survival of banking institutions listed on the Indonesia Stock Exchange (IDX) from 2015 to 2024, using the Altman Z''-Score to assess financial distress and the Cox Proportional Hazards Model to evaluate the impact of macroeconomic factors such as inflation, interest rates, and economic growth on their survival probability. Methodology/approach – A quantitative research approach was employed, using financial data from annual reports of banking institutions listed on the Indonesia Stock Exchange (IDX) for the 2015–2024 period. Financial distress was measured using the Altman Z''-Score, while survival probability was assessed using the Cox Proportional Hazards Model. Macroeconomic variables—including inflation, interest rates, and economic growth—were incorporated to analyze their influence on survival of distress banks. Purposive sampling was used to select banks that consistently published financial statements throughout the study period. Findings – It was found that several banking institutions listed on the IDX experienced financial distress during the 2015–2024 period, as indicated by low Altman Z''-Scores. The survival analysis revealed that inflation and interest rates had a statistically significant negative effect on the survival probability of distressed banks, while economic growth had a positive impact. Among the three macroeconomic variables, interest rates were the most dominant factor influencing bank survival. Novelty/value – This study offers a novel integration of Altman Z''-Score and Cox Proportional Hazards Model to assess bank survival under macroeconomic pressure, providing insights for early detection of financial distress in Indonesian banks.